2022
DOI: 10.1002/hsr2.930
|View full text |Cite
|
Sign up to set email alerts
|

Current status of robot‐assisted surgery in the clinical application of trauma orthopedics in China: A systematic review

Abstract: Background and Aims To elaborate on the development and characteristics of trauma orthopedic robots and their real curative effect in a clinical application through the collection and analysis of relevant literature and reported clinical results. Method We conducted the Embase, ScienceDirect, Pubmed, Medline, Wanfang, CNKI, and VIP search of the literature on robotic‐assisted surgery in trauma orthopedics in China. We combined search terms with “robotic surgery/artificial intelligence surgery/navigation surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 28 publications
(65 reference statements)
2
5
0
Order By: Relevance
“…Additionally, we found that the TiRobot‐assisted group is significantly better than the freehand group in terms of the fluoroscopy frequency of the surgeons and the patient, the fluoroscopy exposure time of the surgeons and the patient, operation time, and blood lost, indicating its advantages in reducing trauma and radiation damage. Several studies have reported results consistent with our findings 2,12,35 …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Additionally, we found that the TiRobot‐assisted group is significantly better than the freehand group in terms of the fluoroscopy frequency of the surgeons and the patient, the fluoroscopy exposure time of the surgeons and the patient, operation time, and blood lost, indicating its advantages in reducing trauma and radiation damage. Several studies have reported results consistent with our findings 2,12,35 …”
Section: Discussionsupporting
confidence: 93%
“…In other words, it might support the rapid and comprehensive recovery of FFP patients. A recent study in China showed that robot‐assisted surgery has obvious advantages in terms of accuracy, stability, and reduction of intraoperative radiation exposure, but the benefits are still inconclusive in terms of functional recovery 12 . We believe that our findings can be used as an update and supplement to the above conclusions.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In other words, it may provide a strong guarantee for the rapid and comprehensive recovery of FFP patients. A recent study from China has shown that Robot-assisted surgery has clear advantages in accuracy, stability, and reducing intraoperative radiation exposure, but there is no nal conclusion about functional recovery 7 . We believe that our ndings can be used as an update and supplement to the above conclusions.…”
Section: E Cacy and Safety Of Tirobot-assisted Surgerymentioning
confidence: 99%
“…Over the years, for the treatment of this disease, the surgical mode has changed from the traditional open surgery with high risk and many complications to minimally invasive surgery, and manual screw implantation and internal xation has been widely used in clinical practice. In recent years, robot-assisted surgery has been applied to a variety of orthopedic procedures, including joint replacement, spine surgery, bone tumor surgery, arthroscopic surgery, and fracture xation [7][8][9][10] , and has achieved accelerated postoperative recovery. Wu et al 11 took the lead in using Tianji Orthopedic robot system to carry out robot-assisted percutaneous minimally invasive pelvic xation.…”
Section: Introductionmentioning
confidence: 99%